Analysis of Digital Competence of Teachers of Leading Schools Based on TPACK: A Case Study at SD Negeri 3 Cakul - Bambang Eko Basuki; Dian Septi Nur Afifah; Fajar Hendro Utomo; Muhammad Anasrulloh (SAGA: Journal of Technology and Information System, 2025)
This study investigates the digital competence of Penggerak School teachers at SD Negeri 3 Cakul, Trenggalek Regency, through the Technological Pedagogical Content Knowledge (TPACK) framework, focusing on Technological Knowledge (TK), Pedagogical Knowledge (PK), and Content Knowledge (CK). Using a qualitative case study approach, data were gathered through in-depth interviews, classroom observations, and documentation analysis involving eight teachers. Results indicate that TK scores ranged from 84% to 92%, reflecting good to excellent command of digital devices and applications, despite unstable internet connectivity in this rural setting. PK competence was demonstrated through varied instructional strategies, technology-integrated class management, and holistic assessment approaches. CK competence showed comprehensive mastery of curriculum-aligned subject matter, contextualised with students' daily lives, and enriched through validated digital sources. Collectively, these three foundational domains underpin effective TPACK integration. The findings validate the TPACK framework in the Indonesian primary school context and suggest that digital competence development depends not only on infrastructure but also on collaborative learning culture and instructional leadership.